2016
DOI: 10.4311/2015mb0128
|View full text |Cite
|
Sign up to set email alerts
|

Speleomycology of air and rock surfaces in Driny Cave (Lesser Carpathians, Slovakia)

Abstract: This paper is a speleomycological report from Driny Cave in the Lesser Carpathian Mountains, Slovakia. The samples were collected in July 2014 from one location outside and five locations inside the cave. To examine the air, the Air Ideal 3P sampler was used. Samples from the rock surfaces were collected using sterile swabs wetted in physiological saline (0.85% NaCl). The density of filamentous fungi isolated from the air inside and outside the cave ranged from 89.6 to 1284.7 colony-forming units per 1 m 3 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Most of the abundant genera observed in our study were also common in other caves, such as Acremonium , Alternaria , Aspergillus , Cephalotrichum , Cladosporium , Fusarium , Penicillium and Trichoderma (Popović et al, ; Vanderwolf et al, ; Zhang et al, ). Talaromyces , which was dominant in rock samples in this study, was also observed by Ogórek, Dylag, Visnovska, Tancinova, and Zalewski () and Ogórek, Višňovská, and Tančinová (). However, we also found uncommon fungi in this study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Most of the abundant genera observed in our study were also common in other caves, such as Acremonium , Alternaria , Aspergillus , Cephalotrichum , Cladosporium , Fusarium , Penicillium and Trichoderma (Popović et al, ; Vanderwolf et al, ; Zhang et al, ). Talaromyces , which was dominant in rock samples in this study, was also observed by Ogórek, Dylag, Visnovska, Tancinova, and Zalewski () and Ogórek, Višňovská, and Tančinová (). However, we also found uncommon fungi in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Talaromyces, which was dominant in rock samples in this study, was also observed by Ogórek, Dylag, Visnovska, Tancinova, and Zalewski (2016) and Ogórek, Višňovská, and Tančinová (2016). However, we also found uncommon fungi in this study.…”
Section: Community Compositionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is confirmed by the results of these studies. However, it should be emphasized that the numbers of culturable fungal spores detected in the external and internal air of the Demänovská Ice Cave were at much lower levels than in other Slovakian caves (Ogórek et al 2016b , c , d ). Moreover, they did not exceed the limit of fungal air quality, which, e.g., according to the American Industrial Hygiene Association should not be higher than 1000 airborne spores per m 3 (Choi et al 1999 ).…”
Section: Discussionmentioning
confidence: 80%
“…Particularly noteworthy are the species of Basidiomycota, because these fungi grow slowly in vitro (Vanderwolf et al 2013 ). On the other hand, currently approximately 39 genera of fungal spores have been detected in the air of Slovakian caves (Nováková 2009 ; Ogórek et al 2016a , b , c , d ). The air samples of the Demänovská Ice Cave contained 9 genera among them.…”
Section: Discussionmentioning
confidence: 99%